Identify the Value(s) of the Variable that Makes It Undefined

Mathematics
Tutor: None Selected Time limit: 1 Day

Write the value or values of the variable that makes the denominator zero. Then solve the equation.

3/x = 9/8x + 3.

Sep 1st, 2014

I am not sure about the equation, so will solve 3 options.

Option 1:  3/x = 9/(8x + 3)

On the left hand side x=0 will make denominator zero.

On the right hand side denominator equal zero will mean
8x + 3 = 0  or  8x + 3 - 3 = 0 - 3  or  8x = -3  or x = -3/8

So x=0 and x=-3/8 make denominator (one of them at a time) equal to zero.

To solve this, make it to common denominator

3(8x+3) / (x(8x+3)) = 9x / (x(8x+3))

Move everything to one side

( 3(8x+3) - 9x ) / (x(8x+3)) = (9x-9x) / (x(8x+3)) 

Simplify

(24x + 9 - 9x) / (x(8x+3)) = 0

(15x + 9) / (x(8x+3)) =0

The fraction can be zero only if the numenator is zero

15x + 9 = 0  or  15x = -9  or  x = -9/15 = -3/5 = -0.6


Option 2:  3/x = (9/(8x)) + 3

On the left hand side x=0 will make denominator zero.

On the right hand side 8x=0 will make denominator zero, which also possible only when x=0.

To solve this, make it to common denominator

3*8 / (8x) = (9/(8x)) + 3*(8x)/(8x)  or  24 / (8x) = (9/(8x)) + (24x/(8x))

Move everything to one side (right instead of left as in previous case)

(24-24)/(8x) = (9 + 24x -24)/(8x)  or  0 = (24x - 15)/(8x)

The fraction can be zero only if the numenator is zero

24x - 15 = 0  or  24x = 15  or  x = 15/24 = 5/8 = 0.625


Option 3:  3/x = x*(9/8) + 3

The only denominator here is on the left hand side of equation and to make it zero means x=0

To solve this let us get it to common denominator

3*8/(8x) = (9*x*x)/(8x) + (3*8x)/(8x)  or  24/(8x) = (9x^2)/(8x) + (24x)/(8x)

Move everything to one side (right hand side)

(24-24)/(8x) = (9x^2 + 24x -24)/(8x)  or  0 = (9x^2 + 24x -24)/(8x)

The fraction can be zero only if the numenator is zero

9x^2 + 24x - 24 =0  or (divide by 3)  3x^2 +8x - 8 = 0

To solve quadratic equation let us find discriminant:

D=8^2 - 4*3*(-8)=64 + 96 = 160 = (4 * root(10))^2

The solutions are

x = (-8 + 4 * root(10))/(2*3) = (-4 + 2 * root(10)) / 3 
and  
x = (-8 - 4 * root(10))/(2*3) = (-4 - 2 * root(10)) / 3

Sep 2nd, 2014

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Sep 1st, 2014
...
Sep 1st, 2014
Mar 30th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer